Case studies: Primary health service delivery models for the Francophone minority - Entités de planification des services de santé en français 1 et 2(Érié St. Clair / Sud-Ouest et WaterlooWellington, Hamilton, Niagara, Haldimand Brant) Et le Réseau Franco - Santé du Sud de l’Ontario (2016)
In several regions of the province, Francophones are in a minority situation. In several places, health services in French are minimal or even non-existent. Many stakeholders are trying to find solutions to improve or implement health services in French. Often these solutions are not always easy to identify or put in place. In this context, the Erie St. Clair/SouthWest French Language Health Planning Entity has used the services of a consultant who did an analysis of best practices in minority situations across North America and in other countries. This first analysis consists of a brief description of 352 practices developed to meet the needs of minority populations receiving few, if any, health services in their communities. Following this report, we have continued this research jointly with the Waterloo Wellington, Hamilton, Niagara, Haldimand Brant Entity2 and the French Health Network of Central Southwestern Ontario. Our purpose was to be able to identify 5 or 6 best practices in minority situations that might be applicable in our respective regions under the subject areas: primary health care, seniors care, mental illness and chronic disease. Each of the partners could study identified practices and ask more detailed explanations on certain practices that seemed more appropriate to respond to their local needs.
pages: